Dynamical in-situ observation of the lyophilization and vacuum-drying processes of a model biopharmaceutical system by an environmental scanning electron microscope - Vetráková, Ľubica; Neděla, Vilém; Runštuk, Jiří; Tihlaříková, Eva; Heger, Dominik; Shalaev, Evgenyi (International journal of pharmaceutics, 2020)
The paper discusses the real-time monitoring of the changing sample morphology during the entire lyophilization (freeze-drying) and vacuum-drying processes of model biopharmaceutical solutions by using an environmental scanning electron microscope (ESEM); the device's micromanipulators were used to study the interior of the samples in-situ without exposing the samples to atmospheric water vapor. The individual collapse temperatures (Tc) of the formulations, pure bovine serum albumin (BSA) and BSA/sucrose mixtures, ranged from -5 to -29 °C. We evaluated the impact of the freezing method (spontaneous freezing, controlled ice nucleation, and spray freezing) on the morphologies of the lyophiles at the constant drying temperature of -20 °C. The formulations with Tc above -20 °C resulted in the lyophiles' morphologies significantly dependent on the freezing method. We interpret the observations as an interplay of the freezing rates and directionalities, both of which markedly influence the morphologies of the frozen formulations, and, subsequently, the drying process and the mechanical stability of the freeze-dried cake. The formulation with Tc below -20 °C yielded a collapsed cake with features independent of the freezing method. The vacuum-drying produced a material with a smooth and pore-free surface, where deep cracks developed at the end of the process.
Keywords: farmaceutická chemie; Environmental scanning electron microscopy; vakuum; Sucrose; Microscopy, Electron, Scanning; Bovine serum albumin; Desiccation; mikroskopie elektronová rastrovací; sérový albumin hovězí; Chemistry, Pharmaceutical; Serum Albumin, Bovine; Vacuum; Freeze-drying; Cold Temperature; Freeze Drying; Vacuum-drying; vysoušení; lyofilizace; nízká teplota; sacharosa